Penggunaan Trichokompos Jerami Padi Dengan Berbagai Stater Trichoderma Sp Untuk Pertumbuhan dan Mengendalikan Penyakit Busuk Pelepah dan Blas Pada Padi Muda - Ayub, Muhammad; Elfina S, Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of the research was to determine the effect of rice straw composting by various Trichoderma spp as starter on rice seedling growth and to control stem rot and blast disease in rice . Experimental study was conducted using completely randomized design with 5 treatments and 3 replications. The treatments were application of trichocompost is T0= Without trichocompost, T1=trichocompost pseudokoningii, T2=trichocompost harzianum, T3=trichocompost koningii, and T4= trichocompost viride. The results showed that utilization of trichocompost did not effect soil emergence of rice seed, but resulted better rice plant growth increased growth plant rice as indicated by teller plant height, greater plant dry weight and number of tilllers of rice. Trichocompost pseudokoningii and trichocompost harzianum performed better control to the diseases than trichocompost coningii and trichocompos viride as indicated by decreasing the intesity of both disease attacks. Keywords: Trichoderma spp., rice straw trichocompost, Rhizoctonia solani, Pyricularia oryzae.